Diverse Linguistic Development in Prelingually Deaf Children with Cochlear Implants - Pia De Stefano; Francesco Pisani; Giuseppe Cossu (Behavioural Neurology, 2019)
The advent of cochlear implants has enormously improved the quality of sensory perception in deaf children. Notwithstanding these advantages, the current literature shows a substantial variability in language proficiency among implanted children. This case series explores the variability of language acquisition in congenitally deaf children with cochlear implants. We report 4 prelingually deaf children (mean age=10.5; SD=1.08), affected by a genetically determined bilateral deafness, due to GJB2 gene mutation Cx26. Each implanted child underwent a systematic assessment of speech perception and production, as well as of lexical, morphologic, and syntactic skills in both comprehension and production. Notwithstanding similar clinical histories and similarly good postimplant pure-tone audiometry, two of the four children fared very poorly in speech audiometry, whereas the other two children gained very good results. We suggest that the language impairment detected in (some) implanted children may not be fully accounted for by pure auditory thresholds and that may be the outcome of concomitant damage to core components of the child’s linguistic brain.